Dissection in biology education compared to alternative methods in terms of their influence on students’ emotional experience - Kaiser, Lisa-Maria; Polte, Sabrina; Kirchhoff, Tim; Großmann, Nadine; Wilde, Matthias (Frontiers in Psychology, 2023)
Dissecting animal organs is a method of biology teaching that offers a direct and authentic view into morphological structures and enables hands-on activity and multisensory experiences. However, the dissection process is often associated with certain (negative) emotions that might hinder successful learning. One such emotion that is particularly common during dissection is disgust. Experiencing disgust can negatively affect emotional experiences and motivational variables. Consequently, alternatives for dissection in biology lessons are being sought. In this study, the method of dissection is compared with two common methods of teaching the anatomy of the mammalian eye: watching a video and working with an anatomical model. The focus of the comparison is on the influence on the following emotional qualities of experience: perceived disgust, perceived interest, well-being and boredom. Two hundred and eighteen students (Mage = 14.19, SDage = 1.02 years, 52% female) from secondary schools in Germany participated in a two-hour lesson on the anatomy of the mammalian eye using one of the three aforementioned teaching methods. Our results show that perceived disgust was higher for the dissection group than in the ones that worked with a video or a model. We found that dissecting and watching a video led to a similar level of interest, well-being, and boredom. The anatomical model was perceived as less disgusting but more boring than dissection. The detailed videos of a dissection seem to offer similar positive emotional qualities of experience when compared to dissecting in class.